Early cardiovascular involvement in Chronic Obstructive Pulmonary Disease - Malerba, M.; Romanelli, G. (Monaldi Archives for Chest Disease, 2016)
Cardiovascular (CV) disease represents a considerable risk factor in terms of both morbidity and mortality in elderly patients with chronic obstructive pulmonary disease (COPD). In fact, there is a considerable evidence of this association: for only 20 years forced expiratory volume in 1 second (FEV1) has been considered as predictive of cardiovascular mortality especially in elderly patients. At present, the emerging evidence suggests that hypoxia, systemic inflammation, oxidative stress may cause an early sub-clinical cardiovascular involvement in patients with COPD. Aging is a selective process dramatically affecting certain portions of the cardiovascular system for example: diminished beta-adrenergic responsiveness, increased myocardial and vascular stiffness, decreased arterial baroreflex, vagal outflow and compromission of diastolic function. The nature of these interactions is complex and involves not only mechanisms of aging but also multiple defined and undefined (e.g., genetic) risk factors. Cardiovascular diseases are the main causes of mortality among the subjects with impaired lung function. Even mild reductions in expiratory flow volumes amplify the risk of ischemic heart diseases, strokes, and sudden cardiac deaths 2-to 3-fold, independent of other risk factors. The mechanism or mechanisms responsible for this association, however, remain largely unknown.